PENGARUH PERUBAHAN POROS ENGKOL STANDAR DAN MODIFIKASI PADA DAYA DAN TORSI TERHADAP PERFORMA MESIN SEPEDA MOTOR HONDA GL-100 MENGGUNAKAN BAHAN BAKAR PERTAMAX PLUS - Henry Pradana; Khoirul Anam; Towijaya Towijaya (Surya Teknika: Jurnal Ilmiah Teknik Mesin, 2022)
Technological developments that continue to develop today are increasingly making it easier for humans to do their jobs, as well as what is happening in the automotive world with the new technology it will make it easier for mechanics to do their jobs because of demands from consumers or the desires of the mechanics themselves who continue to grow to know the influence of standard crankshaft changes and modifications. crankshaft crf230 xiema diablo on power and torque on a motorcycle honda gl-100. This test was carried out using a dynotest tool, the effect of changing the standard crankshaft and modifications on power and torque on a motorcycle honda gl-100 using Pertamax Plus fuel with the result 25.7 Hp at engine speed is 8193Rpm, while the maximum torque results is 22.56 Nm at engine speed of 8979 Nm.Keywords: Crankshaft, Power and Torque